P81 Forecasting trends in disability in england and wales to 2030: a modelling study. (2nd September 2017) - Guzmán-Castillo, M; Ahmadi-Abhari, S; Bandosz, P; Capewell, S; Steptoe, A; Singh-Manoux, A; Kivamaki, M; Shipley, MJ; Brunner, EJ; O'Flaherty, M
Abstract : Background: Reliably estimating the future burden of disability in our ageing societies is crucial. However, previous forecasts failed to consider the potentially significant impact of trends in disease incidence, both up and down. Our aim is thus to forecast the future disability burden in England and Wales to 2030, while taking into account ongoing trends in CVD and dementia incidence. Methods: We developed and validated the IMPACT-Better Ageing Model. Using evidence-based age-sex- and year-specific transition probabilities, this probabilistic model tracks the England and Wales population aged 35–100 years through ten health states (notably CVD, cognitive impairment, disability, dementia and death). We projected continuing declines in dementia incidence, CVD incidence and mortality rates through to 2030 (based on ELSA analysis and consistent with cohorts elsewhere). We then estimated future disability prevalence, distinguishing four types of disability: CVD-related, dementia-related, CVD and dementia-related and Non-CVD/Non-dementia disability. Results: England and Wales will continue its transition towards a much older population structure. Between 2015 and 2030, the number of people aged over 65 years will increase by approximately 33.2% (95% uncertainty interval 32.2%–34.1%) while the very old population (over 85) will increase by some 68.3% (63.2%–73.0%) The standardised prevalence of disability among adults aged over 65 years will stay constant at around 21.4% (21.2%–21.6%). However, the number of people living with disability will rise by 40.1% from 2.3 million to 3.2 million. In 2030, Non-CVD/Non-dementia related disability will account for approximately two-thirds of disabled people aged 65–84, (the absolute numbers increasing in approximately 52% from 2015). Dementia-related disability will also increase by some 51% (44.4%–58.8%). Conversely, CVD-related disability will decline by approximately 27% (22.2%–30.0%). Among the very old aged over 85 years, 40% of the cases of disability in 2030 will be attributable to dementia, representing a 113.4% (102.6%–123.6%) increase since 2015. Non-CVD/Non-dementia disability will rise even more, by approximately 159.2% (148.4%%–169.1% ). However, CVD-related disability cases, will increase by just 2.8% (-1.4%–7.0%). Conclusion: The number of older people with care needs will expand by approximately one third by 2030, mainly reflecting population ageing rather than higher prevalence rates of disability. This will pose a substantial societal challenge and increase the need for cost-effective long-term care in all its forms: institutional, home-based and informal. Future research on the potential benefits of effective prevention strategies might therefore concentrate on the shared determinants of these non-communicable diseases.